2017
DOI: 10.1111/iej.12760
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study assessing the effect of coronal tooth structure loss on the outcome of root canal retreatment

Abstract: The loss of tooth structure volume is an objective parameter that can be used to predict the probability of success of root canal retreatments. At 1-year follow-up, the percentage of unfavourable outcomes of root canal retreated teeth was significantly higher when less than 30% of the original tooth tissue structure was present at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 51 publications
(110 reference statements)
0
49
0
Order By: Relevance
“…Al‐Nuaimi et al . () concluded that a favourable outcome was more likely when at least 30% residual tooth structure was present at the commencement of root canal retreatment. In a pooled analysis of 354 root filled teeth (123 primary treatments and 231 retreatments), the success rate for root canal treatment was lower when assessed using CBCT compared to PR.…”
Section: Assessment Of Periapical Periodontitismentioning
confidence: 99%
“…Al‐Nuaimi et al . () concluded that a favourable outcome was more likely when at least 30% residual tooth structure was present at the commencement of root canal retreatment. In a pooled analysis of 354 root filled teeth (123 primary treatments and 231 retreatments), the success rate for root canal treatment was lower when assessed using CBCT compared to PR.…”
Section: Assessment Of Periapical Periodontitismentioning
confidence: 99%
“…, Al‐Nuaimi et al . , Nascimento et al . ) only periapical radiographs have been used in most previous outcome studies.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the clinical studies assessing the outcome of root canal treatment have only analysed the effect of individual variables on post-treatment healing (Ørstavik et al 2004). In order to improve understanding on this essential issue, several clinical studies have evaluated multiple predictors of outcome (Friedman et al 2003, de Chevigny et al 2008, Liang et al 2011, Fern andez et al 2013, Touboul et al 2014, Davies et al 2015, Al-Nuaimi et al 2017). However, except for some studies (Patel et al 2012, Fern andez et al 2013, Davies et al 2015, Al-Nuaimi et al 2017, Nascimento et al 2018) only periapical radiographs have been used in most previous outcome studies.…”
mentioning
confidence: 99%
“…Ethical approval by the Health Research Authority, UK (IRAS: 233932) was gained to collect patient data from the clinical records of patients who had already been successfully recruited as part of a prospective cohort study, which investigated the outcome of retreated posterior teeth with varying degrees of coronal tooth structure loss (Al‐Nuaimi et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of residual tooth structure is one of the most important parameters determining the survival of (re-)treated teeth (Reeh et al 1989, Gulabivala 2004, Nagasiri & Chitmongkolsuk 2005, Ng et al 2006, Creugers et al, 2012, Al-Nuaimi et al 2017. Teeth diagnosed with endodontic disease often lack structural integrity and are compromised as a result of caries, existing restoration(s), cracks and fractures (Larson et al 1981, Eakle et al 1986, Tan et al 2006).…”
Section: Introductionmentioning
confidence: 99%